FAKTOR YANG MEMPENGARUHI RISIKO KREDIT DAN YIELD OBLIGASI PADA PERUSAHAAN PERBANKAN - Asih Widajati (University of Merdeka Malang, 2010)
Investing in bonds was preferred by investors with the reason that the bonds offer the returns that arepositive with fixed income so that more bond guarantee from the stock. Investors choose the bonds withrank considered (rating) of bonds and bond return (expressed in yield). This study aimed to analyze theinfluence. corporate governance of credit risk, the influence of corporate governance on bond yield, theeffect of credit risk on the bond yield. The used data was secondary data. The research population was banksthat issue bonds from 2008 to 2010. Sampling was done by using purposive sampling technique so thatthere were 7 banks that meet the condition sets in the sample. Tests analysis used path analysis. The resultsshowed that corporate governance the effect to credit risk and yield bonds. The results showed that bondwas the choice of investors to invest.